"Making a difference" – Medical students' opportunities for transformational change in health care and learning through quality improvement projects. Issue 1 (December 2016) - Bergh, Anne-Marie; Bac, Martin; Hugo, Jannie; Sandars, John
Abstract Background Quality improvement is increasingly becoming an essential aspect of the medical curriculum, with the intention of improving the health care system to provide better health care. The aim of this study was to explore undergraduate medical students' experiences of their involvement in quality improvement projects during a district health rotation. Methods Student group reports from rotations in learning centres of the University of Pretoria in Mpumalanga Province, South Africa were analysed for the period 2012 to 2015. Interviews were conducted with health care providers at four learning centres in 2013. Results Three main themes were identified: (1) 'Situated learning', describing students' exposure to the discrepancies between ideal and reality in a real-life situation and how they learned to deal with complex situations, individually and as student group; (2) 'Facing dilemmas', describing how students were challenged about the non-ideal reality; (3) 'Making a difference', describing the impact of the students' projects, with greater understanding of themselves and others through working in teams but also making a change in the health care system. Conclusion Quality improvement projects can provide an opportunity for both the transformation of health care and for transformative learning, with individual and 'collective' self-authorship.